Case Study: Analysis of Factors Affecting Marriage Satisfaction in Married Couples During Pandemic: Case Study: Analysis of Factors Affecting Marriage Satisfaction in Married Couples During Pandemic - Emy Rosiana; Ayu Arba Zaman; Fitri Lutfiani; Megawati Simanjuntak; Yulina Eva Riany (Journal of Family Sciences, 2022)
Marriage is a sacred moment because it is considered a symbol of the transformation of parent’s responsibility to the husband who is the head of the household. Marriage adjustment during the pandemic and the division of roles of gender in family life must be well intertwined in order to create a sense of satisfaction in marriage, especially for married couples during the pandemic. The study aims to analysis the marriage satisfaction of married couples during the pandemic. The study is a qualitative study using an impressive type of case study. sampling technique with the wife of the couple who conducted a wedding during the pandemic as the subject. The data retrieval technique involves semi-structured interviews using the interview guidelines and analysis through the three-grooved technique of data reduction, data presentation, deduction/verification. Research has shown that marriage satisfaction of married couples during the pandemic is affected by internal factors such as family relationships, social and external environments, free time between couples, preparations for childbirth, and parenting. The relationship between the spouse and the family of both spouses works well, which promotes satisfaction in the marriage.